2015
DOI: 10.1021/acs.accounts.5b00404
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Inverted Planar Structure of Perovskite Solar Cells

Abstract: Inorganic-organic hybrid perovskite solar cells research could be traced back to 2009, and initially showed 3.8% efficiency. After 6 years of efforts, the efficiency has been pushed to 20.1%. The pace of development was much faster than that of any type of solar cell technology. In addition to high efficiency, the device fabrication is a low-cost solution process. Due to these advantages, a large number of scientists have been immersed into this promising area. In the past 6 years, much of the research on pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
377
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 595 publications
(400 citation statements)
references
References 46 publications
9
377
0
1
Order By: Relevance
“…c | A photovoltaic PEC device for water splitting using mesoporous materials as hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) catalysts. n-type materials as bottom and top charge transport layers), with fullerene as the electron transport layer, as a result of ion-movement stabilization 62 . The long-term stability of perovskite solar cells is of increasing interest because of the high PCEs reported.…”
Section: Solar Cellsmentioning
confidence: 99%
“…c | A photovoltaic PEC device for water splitting using mesoporous materials as hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) catalysts. n-type materials as bottom and top charge transport layers), with fullerene as the electron transport layer, as a result of ion-movement stabilization 62 . The long-term stability of perovskite solar cells is of increasing interest because of the high PCEs reported.…”
Section: Solar Cellsmentioning
confidence: 99%
“…344 After a few years of development only, the perovskite solar cells reach record efficiencies of about 20%. 345 Meanwhile, other potentialities of halide perovskites have been explored. Thanks to their high absorption cross-section, 346 near unity fluorescence quantum efficiency 347,348 and exceptional charge diffusion length, 349 halide perovskites, under bulk, thin films or nanoparticles shapes are a potential game changer in diverse applications such as light-harvesting, 350 photodetection 351 or light-emitting devices.…”
Section: Perovskitesmentioning
confidence: 99%
“…Noel et al [153] and Dane et al [154] used Lewis bases such as pyridine to treat the perovskite films in order to reduce recombination centers, enhancing the photoluminescence intensity and lifetime. In addition, it has been widely observed that [6,6]-phenyl-C 61 -butyric acid methyl ester (PCBM) molecules, [155,156] either as an interlayer or mixed as bulk heterojunction structure, are able to passivate defects and alleviate or even eliminate hysteresis. [76] Although the defect passivation process significantly enhances the device performance and decreases the hysteresis, it is found that the time interval for charge trapping and detrapping ranges within milliseconds, [157] or even nanoseconds, [158] which is much shorter than the typical time for the hysteretic behavior.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%